Settlement of Disputes Between Foreign Investors and State by Arbitral Tribunals Established under the 1965 Washington Convention (ICSID) - Khvedelidze, Mate (Alternative Dispute Resolution Yearbook, 2022)
Establishing effective means of dispute resolution between investor and state is important aspect of attracting investors. In general, the countries which provide predetermined transparent procedures are preferred by the investors. It can be said, that together with legal guarantees, existence of international dispute resolution procedures are equally important for the investors. Following is discussed in the article: Origins of international procedures of dispute resolution between investor and state. Establishing jurisdiction by ICSID arbitral tribunals, forms and procedures for state consent to ICSID arbitration, initiation of an arbitration claim, procedure for appointing arbitrators, rules of arbitration hearings, evidence in arbitration procedures, application for securing a claim by arbitrator and requesting information from the third parties, making a decision by the arbitral tribunal. Issue of prerequisites for admissibility of a counterclaim filed by the state against the investor is also discussed in the article. Reviewing of the abovementioned issues is equally important for providing protection of investor rights and for implementing dispute prevention mechanisms.